Memahami Ancaman Venture Capital Zombie Terhadap Stabilitas Ekonomi: Analisis Dampak Modal Ventura Yang Tidak Produktif Pada Keseimbangan Finansial Global - Mutia Usnita; Ending Sution; Amanda Widyastuti (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This research examines the "Venture Capital Zombie" phenomenon and its implications for global economic stability. "Venture Capital Zombie" refers to venture capital firms that continue to operate despite being unable to generate significant profits or innovations. This study employs secondary data analysis, literature review, and policy analysis to minimize the economic impact of zombie venture capital. The research findings indicate that this phenomenon can hinder innovation, create resource allocation distortions, and increase systemic risk. The Financial Services Authority (OJK) in Indonesia has identified this issue and is preparing regulations to address it. This study suggests the need for stricter supervision, investment diversification, and better risk mitigation strategies to reduce the negative impact of "venture capital zombies." The conclusions of this research provide valuable insights for policymakers and financial practitioners in efforts to maintain global economic stability.